Pengaruh Konten Game Akun Miawaug di Youtube Terhadap Minat Menonton Subscribers - Stefanus; Salman (UNIVERSITAS KALBIS, 2022)
Social media is a site and application that involves internet-based technology. One example for rapidly growing new media is YouTube. YouTube is a social media that delivers messages digitally and can be watched by many people. YouTube is a place to share videos online with other people. This study is determining the effect of game content YouTube Miawaug on subscribers viewing interest. This study a positivism paradigm with quantitative approach. The method use a survey method with questionnaire. Type of research is an explanative. This theory is theory stimulus-response theory. The results of test correlation of Pearson's Product Moment this a sig. 0.762, which means that the level of the relationship between the independent variables and dependent variable is strong level of relationship. Based on the results of the coefficient determination test, the effect of game content on YouTube Miawaug on the interest in watching subscribers with a percentage 58.1%.